KONSTRUKTIVISME SOSIAL DALAM PEMANFAATAN CANVA SEBAGAI MEDIA PEMBELAJARAN AGRIBISNIS: STUDI KASUS DI SMK NEGERI 6 TAKALAR - Rasdin, Sunarti; Farida Febriati (STKIP Subang, 2026)
This study aims to analyze the psychological phenomena of vocational students' learning through the lens of Vygotsky's Social Constructivism theory in the context of using Canva as an Agribusiness learning medium. A descriptive qualitative method with a case study approach was employed through two direct classroom observation sessions in Grade X Agribusiness. Results reveal a gap between Canva's interactive potential and its one-way implementation, indicating that the principles of Zone of Proximal Development (ZPD), scaffolding, and social mediation remain underutilized. These findings suggest that passive technology use inhibits active knowledge construction. This article recommends transforming Canva from a presentation medium into a collaborative constructive platform through think-pair-share strategies, visual artifact peer review, and advance organizers grounded in local agribusiness contexts.